Pengaruh Label Halal dan Tanggal Kadaluarsa Terhadap Keputusan Pembelian Prouduk Mie Instan di Kelurahan Pulo Padang - Ritonga, Nurhamidah; Ulya, Basyarul; Syafriyeti, Rahmi (Innovative: Journal Of Social Science Research, 2025)
Since the majority of Indonesia's population is Muslim, halal labels and expiration dates on food and beverage products are very important when purchasing. This study focuses on people aged 18 and over in Pulo Padang Village who buy instant noodles. This study will investigate how halal labeling and expiration dates affect buyer choices. The data collection method is by using a questionnaire. The results of the study indicate that halal labels and expiration dates influence customer choices when purchasing goods. The results of the determination test were 72.4 percent, with 27.6 percent influenced by external variables that were not studied.